2016
DOI: 10.1097/md.0000000000005542
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 2013 AHA/ACC ASCVD risk scores with behavioral characteristics of an urban cohort in India

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
1
13
0
2
Order By: Relevance
“…Of the 24 studies included in this review, more than half (54%) were conducted in India 36,38,40,42,44,45,47–49,5154 , two each in Pakistan 34,46 and Nepal 33,41 and one each in Sri Lanka 55 , Bangladesh 56 and Afghanistan 37 . One study 57 reported results for five South Asian countries while two studies 39,50 were based in two South Asian countries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 24 studies included in this review, more than half (54%) were conducted in India 36,38,40,42,44,45,47–49,5154 , two each in Pakistan 34,46 and Nepal 33,41 and one each in Sri Lanka 55 , Bangladesh 56 and Afghanistan 37 . One study 57 reported results for five South Asian countries while two studies 39,50 were based in two South Asian countries.…”
Section: Resultsmentioning
confidence: 99%
“…More than half of the studies (14 out of 24) were published between 2001 and 2010. Eighteen of the 24 studies were cross-sectional in design 33,3742,44–49,5357 while the remaining six were matched case-control studies 34,36,50–52,58 . Age was one of the matching variables in all these six studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Andrés-Felipe Villaquiran 1 ; Paola Cuero 1 ; Gineth-Magally Ceron 2 ; Armando Ordoñez 3 ; Sandra Jácome 1 Forma de citar: Villaquiran AF, Cuero P, Ceron GM, Ordoñez A, Jácome S. Características antropométricas, hábitos nutricionales, actividad física y consumo de alcohol en estudiantes universitarios. Salud UIS.…”
Section: Características Antropométricas Hábitos Nutricionales Actiunclassified
“…Las enfermedades no transmisibles (ENT) representan una sobrecarga de morbilidad y mortalidad considerablemente alta a nivel mundial 1 . El aumento de la prevalencia de estas patologías como la diabetes, el cáncer, las enfermedades cardiovasculares y pulmonares crónicas generan un impacto sobre la salud, los sistemas de atención, el costo de los servicios sanitarios y la disminución de los años de vida productiva de una persona 2 .…”
Section: Introductionunclassified